2009
DOI: 10.1080/00036840802600129
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional approaches to poverty measurement: an empirical analysis of poverty in Belgium, France, Germany, Italy and Spain, based on the European panel

Abstract: This article has three goals. First, we wish to compare three multidimensional approaches to poverty and check to what extent they identify the same households as poor. Second, we aim at better understanding the determinants of poverty by estimating logit regressions with five categories of explanatory variables: size of the household, age of the head of the household, her gender, marital status and status at work. Third, we introduce a decomposition procedure proposed recently in the literature, the so-called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…We experiment with a range of values for the threshold, from a relatively low value of 70 percent of the median S i as in D'Ambrosio et al . () and Deutch and Silber (), to a more generous 85 percent of the median S i . In each case the threshold is fixed at a fraction of the median S i in wave 1, in line with our fixed‐in‐real‐terms IP .…”
Section: Data and Definitionsmentioning
confidence: 95%
See 1 more Smart Citation
“…We experiment with a range of values for the threshold, from a relatively low value of 70 percent of the median S i as in D'Ambrosio et al . () and Deutch and Silber (), to a more generous 85 percent of the median S i . In each case the threshold is fixed at a fraction of the median S i in wave 1, in line with our fixed‐in‐real‐terms IP .…”
Section: Data and Definitionsmentioning
confidence: 95%
“…Moreover, many researchers may still prefer to look at multidimensional measures of poverty even if longitudinal consumption measures are available (e.g., Sen, ; Berthoud et al ., ). Instead of consumption, many panel datasets ask questions about deprivation in a number of ‘necessary’ goods and services, and allow for the construction of multidimensional indices of poverty (e.g., Muffels and Fourage, ; Deutsch and Silber, ; Whelan and Maitre, ; D'Ambrosio et al ., , Alkire and Foster, ). Hence, empirical researchers seeking to study the longitudinal aspects of poverty can rely on both the observed individual income sequence and the longitudinal sequence of multidimensional deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…Demir Seker and Dayioglu () propose a decomposition method to examine the factors accounting for changes in absolute poverty rates over the two sub‐periods. D’Ambrosio et al () introduce a decomposition procedure to determine the exact marginal impact of a set of explanatory variables (i.e. household size, age, gender, marital status and occupational status) on poverty using Belgium, France, Germany, Italy and Spain.…”
Section: Longitudinal Studies Of Povertymentioning
confidence: 99%
“…Devicienti (2008) applies the methodology to decompose wage income. In contrast, Kolenikov and Shorrocks (2005), and D'Ambrosio et al. (2004) use the procedure to decompose poverty.…”
Section: Regression‐based Decompositionmentioning
confidence: 99%